103: A Family-Centered Lifestyle Intervention Focused On Milk and Alternatives Reduces Adiposity in Six to Eight Y Old Overweight and Obese Children Compared to Control: Results at Six Months From a RCT. Issue 6 (1st June 2014) - Cohen, TR; Hazell, TJ; Loiselle, S; Kasvis, P; Vanstone, CA; Kim, N; Rodd, C; Weiler, HA
Abstract: BACKGROUND: The association between adiposity and milk and alternative (milk and alt.) intakes in prepubescent children is unclear. OBJECTIVES: This study assessed the impact of a family-based lifestyle intervention on changes in adiposity in overweight (n=14) and obese (n=64) children (age 7.5±0.78 years). DESIGN/METHODS: Children were randomized to control (CTRL) (no intervention), standard (SInt) (two milk and alt./d) or intensive (IInt) (four milk and alt./d) interventions focused on meeting Canada's food guide for healthy eating and the Canadian physical activity recommendations. Measurements for height (Ht; m) and weight (Wt; kg) to compute body mass index for-age- z-scores (BAZ) using WHOAntroPlus Software (WHO 2007), waist circumference (WC; cm) and percentage body fat (%BF) assessed using dual-energy X-ray absorptiometry, were done at baseline and six-month follow up visits. Proc mixed model ANOVAs were computed using SAS (Version 9.3, SAS Inc., Cary, NC). RESULTS: No differences were seen at baseline among groups for BAZ or %BF. At six months, Ht increased compared to baseline (P=0.898) and was not different among groups. Compared to baseline, %BF (−2.4±0.92%; P=0.0015) and BAZ (−0.5±0.08; P<0.001) was reduced only in IInt whereas WC increased only in CTRL (+2.5±1.61 cm; P=0.007). CONCLUSIONS: These preliminary results demonstrate the possible benefits of participating in a lifestyle intervention focused on increased milk and alt and activity guidelines in the context of the family environment. Study funded by the Dairy Research Cluster (Agriculture and Agri-Food Canada, Dairy Farmers of Canada and the Canadian Dairy Commission).